Análise da estabilidade de estruturas pré-moldadas de concreto: influência das ligações semi-rígidas - Jeremias Júnior, Antônio Carlos (2007)
This research comprehends a study of the analysis procedures of the global stability in precast concrete structures, considering the effect of the semi-rigid connections. A Look over in the standards and directives of the precast structures project was necessary specifically on the procedures of global stability verification, recommended by the NBR 6118. Besides, it was looked to identify particular situations where the analysis of the precast concrete structures differentiates of the analysis of the structures cast in place. Such discussion is relevant at the moment of the publication of the new NBR 9062, where the effect of the behavior of the beam-to-column connections must be considered in the analysis of the global stability. In the carried through studies, the frame action proportionate by the bending moment resistant beam-to-column connections is a efficient method of bracing of the structure since that the interdependence of some factors is analyzed as the number of the floors, the stiffness and the cracking of columns and the beams and the fixity factor αR. Finally, examples of numerical application are presented with intention to guide the designer of precast concrete structures in the analysis of structures with semi-rigid connections.